Pre-formulations Study of Active Pharmaceutical Ingredients Amiodaron in the Development of Oral Tablet Pharmaceutical Preparations as an Anti-Arrhythmia Drug - Anindya, Nisrina Raya; Fadiya, Refeyfa Najwa; Palupi, Anindya Taruni; Jannah, Aisa Zahratul; Deandrea, Helena Jessie; Sopyan , Iyan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Amiodaron is a broad-spectrum antiarrhythmic drug that is widely used in the management of various cardiac rhythm disorders, including ventricular and supraventricular arrhythmias. Despite its therapeutic effectiveness, Amiodaron presents complex physicochemical characteristics that pose significant challenges in the development of oral solid dosage forms, particularly tablet preparations. Therefore, a comprehensive pre-formulation study is essential to ensure the development of stable, safe, and effective pharmaceutical products. This study aims to examine the pre-formulation aspects of Amiodaron hydrochloride as a scientific basis for tablet formulation development. The research method employed was a literature-based study focusing on the physicochemical properties of Amiodaron, including ionization constants (pKa), partition coefficients (log P), solubility, dissolution behavior, polymorphism, chemical and physical stability, as well as particle and powder characteristics. Relevant data were obtained from scientific journals, pharmacopeias, and authoritative pharmaceutical references. The results indicate that Amiodaron hydrochloride is classified as a Biopharmaceutics Classification System (BCS) class II drug, characterized by low aqueous solubility and high membrane permeability. The compound is highly lipophilic, weakly basic, and sensitive to environmental factors such as light, heat, and alkaline pH conditions, which may lead to degradation. Furthermore, Amiodaron powder exhibits poor flowability and compressibility, making direct compression during tablet manufacturing difficult. Based on these findings, appropriate formulation strategies are required, including the use of inclusion complexes, hydrophilic polymers, granulation techniques, and careful selection of excipients to enhance solubility, stability, and bioavailability. This pre-formulation study is expected to provide a strong scientific foundation for the development of optimal Amiodaron tablet formulations.